The Influence Of Work Discipline And Emotional Intelligence On The Employees Performance Of J&T Express Kebun Cengkeh Ambon - Chandra, Felix; Maghfirah, Nurul (Jurnal Ekonomi, 2024)
This research aims to reveal the influence and how big an impact work discipline and emotional intelligence have on the level of performance produced by employees of J&T Express Kebun Cengkeh Ambon, a company that provides goods delivery services. A descriptive approach was used to test hypotheses or answer questions about the research subject, with the research focus on J&T Express Kebun Cengkeh employees, totaling 36 people.Using a saturated sampling method, this approach involves the entire population of J&T Express Kebun Cengkeh employees as the main sample. The likert scale is the main measuring tool used by distributing questionnaires to respondents. In processing the collected data, multiple regression analysis was driven by SPSS statistical software as the main tool. Interesting research results show that work discipline has a positive and significant influence on performance, while emotional intelligence makes a positive but not significant contribution to employee performance. This research not only presents findings but also brings an in-depth understanding of the interaction between work discipline, emotional intelligence, and performance in the context of human resource management.